THE INTERSECTION OF PAN-ISLAMISM, NATIONALISM, AND MODERNISM IN AFGHANISTAN’S PRESS IN INDEPENDENCE ERA: A THEMATIC CONTENT ANALYSIS OF AMAN-E-AFGHAN WEEKLY - Qurban Hussain Pamirzad (Institut Agama Islam Negeri Ponorogo, 2024)
This study employed a qualitative thematic content analysis to explore Afghanistan’s press coverage in the independence era to examine the interconnectedness of religion, national identity, and progressiveness. Using 80 issues of the Aman-e-Afghan publication, which was the official organ of Amanullah Khan’s government 1919-1929, this study found that from the content and publishing policy perspective, this publication continued the path of Siraj-ul-Akhbar advocating pan-Islamism, nationalism, and modernism. This study also shows that pan-Islamism advocating Muslim unity in this publication was motivated by the Muslim countries suffering from imperialism, while nationalism was inspired by the desire to build a cohesive nation, although ethnocentric. Additionally, this publication tried to reconcile tradition and modernity by promoting education, lawfulness, and legislation to lead the country toward modernization.